Práctica pedagógica : el caso de un profesor de matemáticas Iniciante - Ruiz Reina, Yexica Adriana (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Eng: The pedagogical practices of a beginning mathematics teacher require analysis since it is not an easy environment and a complex task, and when observing it, many difficulties and obstacles can arise (Perrenoud, 2004; cited in Díaz and Núñez, 2008, p. 50). The research mentioned here aims to determine the characteristics of the pedagogical practice of a beginning mathematics teacher and its (re)signification (Jiménez, 2002); in such a way that aspects of initial and permanent training, professional development and the skills of the mathematics teacher with little experience are evaluated. The purpose is to reflect on the way in which pedagogical practice occurs, the development of knowledge and learning in the classroom, the difficulties and obstacles that occur in this context, taking into account several dimensions: "the teacher's didactic thinking and Planning teaching; educational interaction within the classroom; and reflection on the results achieved” (García, Loredo and Carranza, 2008, p.9). This research has a mixed approach with a predominantly qualitative auto-ethnographic type as a form of social research, because the "researcher has the privilege and responsibility of being subject and object" (Scribano and De Sena, 2009, p.8). Among the results, it was found that the pedagogical practice carried out by a beginner mathematics teacher is characterized by having different didactic approaches, conceptions and representations as well as different obstacles and difficulties since these change or are modified depending on the mathematical object and/or the context in which they are developed, for which the (re)signification under a virtual environment, taking into account the impact of the crisis produced during the COVID-19 pandemic, is an essential and necessary part for mathematical knowledge to be meaningful and is adapted to the needs and environment of the students.